1986
DOI: 10.1007/bf00456122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adrenal steroids on insulin release from cultured rat islets of Langerhans

Abstract: The effect of additions to the culture medium of some natural or synthetic corticosteroid hormones was studied in cultured rat islets of Langerhans. The steroids decreased glucose-induced insulin release. The extent of inhibition by dexamethasone was 18-55%, prednisolone 23%, hydrocortisone 21% and aldosterone 18%. None of them affected the basal secretion of insulin or had any effect on diameter or insulin content of the islet. The inhibitory action of dexamethasone on insulin release was observed in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 10 publications
4
45
1
3
Order By: Relevance
“…The effects of glucocorticoid on insulin secretion are dependent upon the dose and duration of administration [8]. While most studies report inhibition of insulin secretion by glucocorticoids [5,[9][10][11], long-term culture in hydrocortisone [12] and dexamethasone-treatment of islets from adrenalectomised rats [13] increase insulin release. However, transgenic mice overexpressing GR (also known as NR3C1) specifically in the beta cell have impaired glucose tolerance due to decreased insulin release, suggesting a direct inhibitory action of glucocorticoid upon the beta cell [14].…”
mentioning
confidence: 99%
“…The effects of glucocorticoid on insulin secretion are dependent upon the dose and duration of administration [8]. While most studies report inhibition of insulin secretion by glucocorticoids [5,[9][10][11], long-term culture in hydrocortisone [12] and dexamethasone-treatment of islets from adrenalectomised rats [13] increase insulin release. However, transgenic mice overexpressing GR (also known as NR3C1) specifically in the beta cell have impaired glucose tolerance due to decreased insulin release, suggesting a direct inhibitory action of glucocorticoid upon the beta cell [14].…”
mentioning
confidence: 99%
“…The reduced GSIS under 6.3 µM for 2 h culture was also seen with 7.5, 10, 12.5, 15, 20 and 30 mM glucose. These responses were re-established after 4 h. Pred and Hydr also induced decreased GSIS and none of these drugs elicit a decrease in islet insulin content (Pierluissi et al, 1986) …”
Section: Hours To Days Gc Effectsmentioning
confidence: 87%
“…Details regarding GC compounds used, concentrations, duration of treatment, and main effects on -cell function are described in Table 4. The GC-induced reduction in GSIS could not be attributed to decreases in insulin content since it was unchanged or augmented (Pierluissi et al, 1986;Gremlich et al, 1997;Lambillotte et al, 1997;Zawalich et al, 2006), although reduction was also observed under certain conditions (Jeong et al, 2001). It has been shown that presence of DEX in islet or -cell culture medium induces reduction (Gremlich et al, 1997) or no change (Shao et al, 2004) in GLUT 2 protein content, decrease in -cell GK (Shao et al, 2004) and pyruvate dehydrogenase (PDH) (Arumugam et al, 2010) activities, and increased pyruvate dehydrogenase kinase (PDK)-2 mRNA content (Arumugam et al, 2010).…”
Section: Hours To Days Gc Effectsmentioning
confidence: 95%
“…However, such investigations have also produced conflicting results, probably because of various study designs, GC preparations used, dosages, and time of exposure, as well as different characteristics of the studied cells. The majority of studies indicate an inhibitory GC effect on insulin secretion in vitro [50][51][52][53][54][55][56]. The effect is dosedependent and abolished by addition of GR antagonist RU486 to the cell culture [47,[56][57][58][59][60].…”
Section: Inhibitory Glucocorticoid Effect On Insulin Secretion In Vitromentioning
confidence: 99%